Multimorbidity, Trauma Exposure, and Frailty of Older Adults in the Community - Papathanasiou, Ioanna V.; Fradelos, Evangelos C.; Mantzaris, Dimitrios; Rammogianni, Anna; Malli, Foteini; Papagiannis, Dimitrios; Gourgoulianis, Konstantinos I. (Frontiers in Genetics, 2021)
The aim of this study is to investigate the relation between multimorbidity, traumatic events and frailty among older adults in the community. The studied population consisted of 257 older people who were recipients of the services and active members of Open Care Centers for the Elderly (OCCE) of the Municipality of Grevena and meet a set of selection criteria. The collection of the data was carried out using a fully structured questionnaire, which consisted of two sections: a form of individual features and the Tilburg Frailty Indicator (TFI). The sample consisted of 114 men (44.4%) and 143 women (55.6%) aged between 61 and 96 years with an average of 75.12 years. The results showed that the mean scores were 2.70 for the Physical Frailty (standard deviation = 2.16), 1.43 for the Psychological Frailty (standard deviation = 1.21), 1.32 for the Social Frailty (standard deviation = 0.64) and 5.44 for the total Frailty (standard deviation = 3.02). We took into account the cut-off point five of 54.1% (n = 139) in terms of the participants’ frailty. Physical, Psychological, and Total Frailty are related to (a) the presence of two or more chronic diseases or disorders, (b) the experience of a serious illness in the previous year, and (c) the experience of a serious illness of a loved one during the previous year. The outcomes helped to identify frailty syndrome in older people and the factors associated with it.